SISTEM INFORMASI PERPUSTAKAAN BERBASIS WEB PADA MTS RAUDLATUL 'ULUM PABUARAN JAHA CILEGON BANTEN - Darpi Darpi; Teuku Fadjar Shadek; Sawitri Nurhayati; Mochamad Wahyu (Journal of Innovation And Future Technology (IFTECH), 2023)
Library data processing at MTS Raudlatul 'Ulum Pabuaran Jaha is still done manually so it has drawbacks, namely archiving becomes disorganized, messy, and searching for data takes a lot of time. Therefore, it is necessary to have a web-based library information system so that the administration, management and service processes to users are better. The research method used is the waterfall method, which involves the stages of software requirements analysis, system design, writing program code, program testing, and system maintenance. Data collection methods use observation, interviews and questionnaires. The interview method is used to determine user needs, questionnaires are used to test the feasibility of usability aspects, while observation is used to test performance efficiency aspects. The result of this research is a web-based library information system using the PHP programming language and MySQL database server which can optimize library management, increase service efficiency, and meet the needs of library users effectively, so as to improve the learning process in schools.